Contempt of court in Malaysia: a need for a specific legislation / Ellyana Razali, Karimah Ismail and Noor Alwani Othman - Razali, Ellyana; Ismail, Karimah; Othman, Noor Alwani (2007)
This legal research is conducted with an aim to study and analyze the problems faced by Malaysia due to the absence of specific legislation regulating the issue of contempt of court in Malaysia. To this date, no specific legislation has been enacted as yet Therefore this work will focus on the flaws and the weaknesses of the current Malaysian legal system pertaining to the issue of contempt of court The scope of this legal research is on the rules and regulations of contempt of court in Malaysia as it exists today. However, the existing law of contempt in Malaysia has not been developed well therefore this research necessarily involves some comparative study of the corresponding position in other countries such as India and United Kingdom.